2011
DOI: 10.1111/j.1600-0536.2011.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and experimental studies of octocrylene's allergenic potency

Abstract: The clinical studies show that octocrylene is both a photocontact allergen and a contact allergen. Octocrylene's ability to cause contact allergy is probably attributable to its reactivity towards lysine. To be able to understand why octocrylene causes photocontact allergy, further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 37 publications
5
88
0
Order By: Relevance
“…OCR is a worldwide-approved UV filter which is increasingly used in PCPs offering protection against UV-B wavebands (Karlsson et al, 2011). However, this UV filter can be a strong allergen and can lead to contact dermatitis in children and adults (AvenelAudran et al, 2010).…”
Section: Synthetic Organic Uv Filtersmentioning
confidence: 99%
See 1 more Smart Citation
“…OCR is a worldwide-approved UV filter which is increasingly used in PCPs offering protection against UV-B wavebands (Karlsson et al, 2011). However, this UV filter can be a strong allergen and can lead to contact dermatitis in children and adults (AvenelAudran et al, 2010).…”
Section: Synthetic Organic Uv Filtersmentioning
confidence: 99%
“…Avenel-Audran et al (2010) indicated that children and adults with a history of photoallergy from sunscreen products had positive patch and photopatch test reactions to OCR. In addition, Karlsson et al (2011) reported 23 cases of positive patch and photopatch test reactions in patients with a history of reaction to the anti-inflammatory drug ketoprofen. A study in Switzerland by Schlumpf et al (2010) showed that exposure to UV filters through PCP use was correlated with the presence of chemicals in breast milk and they found that OCR and 4-methylbenzylidene camphor were present in 85.2% of the milk samples.…”
Section: Synthetic Organic Uv Filtersmentioning
confidence: 99%
“…Among the newer photoallergens, the NSAID ketoprofen not only induces severe and long-lasting photo-allergic contact dermatitis, but also gives rise to the development of photocontact allergy to the sunscreens benzophenone-3 and octocrylene. For reprint orders, please contact reprints@expert-reviews.com Special Report photodegradation [9,10]. These attractive properties have contributed to its widespread use in sunscreens and cosmetic preparations during the last 10 years and it is approved by the EU [102] and US FDA [11] in concentrations up to 10%.…”
Section: The Contact and Photocontact Allergen Octocrylenementioning
confidence: 99%
“…In the Department of Dermatology, University Hospital K.U. Leuven (Leuven, Belgium), between 2005 and 2011 we have observed 26 cases [10]; five concerned positive patch and 21 photopatch tests, 20 of which proved to be previously photosensitized by ketoprofen, which is a topical NSAID responsible for severe and long-lasting photoallergic contact dermatitis. Such patients frequently develop intolerance to sunscreen products later on.…”
Section: The Contact and Photocontact Allergen Octocrylenementioning
confidence: 99%
See 1 more Smart Citation